Um estudo sobre a distribuição da cota-parte do ICMS no estado de Minas Gerais - Baptista, Juliana Xavier de Castro (2016)
The Federal Constitution of 1988 states in its articles 158-162 which are the intergovernmental transfers of tax revenues between the federal agencies (Federal, State, Federal District and Municipalities). One of these transfers is the transfer of 25% of the ICMS collection of states to municipalities called Cota-part of the ICMS. 25% of the ICMS to be transferred, 75% must be transferred proportionally to the municipal VAF, which is the value added in the transactions regarding the circulation of goods and the rendering of services carried out in their territories, more specifically, the difference between the inputs and outputs of goods and services of the Municipality. In this context, the general objective of this research is to analyze the distribution of quota-part of the ICMS among the 853 municipalities of Minas Gerais, being the main object of this study, the transfer based on VAF which is regulated by Complementary Law 63/1990. The study period was from 2010 to 2013 and the base theory was federalism and fiscal federalism which deals with the division of tax revenues between the federal entities. This was a descriptive, quantitative and desk research conducted from reports provided by the State of MG Finance - SEF / MG, Siconfi / STN and João Pinheiro Foundation - FJP. ANOVA statistical tests were applied in randomized blocks in Nested or hierarchical structure and Skott-Knott test to compare the averages of estimates of Cota-part of the ICMS and VAF between municipalities and development of territories. The results of these tests demonstrated by means of groups formed, there is no similarity between them. To measure the degree of concentration of the variables we calculated the Gini coefficient and plotted the Lorenz curve and to investigate the association between VAF variables, GDP and quota-part of the ICMS it was applied linear correlation test of Spearman. In addition, it was analyzed the composition of the total revenue of the municipalities through graphs and spreadsheets. The results of analyzing the concentration of quota-part of the ICMS in Minas Gerais showed a high degree of concentration, even being included in calculating the 25% allocated to municipalities through the implementation of redistributive criteria of Law 18.030 / 2009 - Law Robin Hood. It also revealed that the concentration is in the municipalities that have greater production of goods and services.